PEMETAAN TEMA PENELITIAN PADA LEMBAGA PENELITIAN UIN SUNAN KALIJAGA YOGYAKARTA TAHUN 1991 - 2012 Mapping of Research theme at Research Institution UIN Sunan Kalijaga 1991-2012 - Muh. Isnanto (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
Research is an important way to produce new knowledge. However, research trend is often influenced by the condition of organization that is in charge with such activity. This study tried to look at the map of the tendency of research results and the research expertise of the lecturers after the changing of IAIN to be UIN Sunan Kalijaga. This study uses a historical approach in order to make such mapping whether it is based on the theme or field of study, type of the research, methodology, approach, and its findings. The research results depict that firstly there is imbalance in terms of theme and type of the researches which are conducted by lecturers at the research institute in UIN Sunan Kalijaga from 1991 to 2012. Secondly, there is a shifting in theme and type of the research before and after the institution become UIN. A policy research has become a trend after it has become UIN in 2004. On the other hand, the number of pure researches decreased significantly and it changed to applied research.